Study of Making of Instant Juicy Tuber Yogurt with Various Concentration of Milk Powder and Starter - Riska Amelia Purba; Herla Rusmarilin; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2013)
This research was conducted to find the concentration of milk powder and starter that suitable for producing instant juicy tuber yogurt with the best characteritics, and also to introduce the refined products from juicy tuber and to find ways of making instan juicy tuber yogurt. This research had been performed using factorial completely randomize design with two factors, i.e the concentration of milk powder (B): 14%,15%,and 16% and the concentration of  starter (S): 2%, 2,5%, 3%, 3,5%, and 4%. Parameters analyzed were total solid, total soluble solid, protein content, total lactic acid, total microbe, solubility, viability, and  organoleptic values (flavour and taste). The results showed that the concentration of milk powder had highly significant effect on total solid, total soluble solid, protein content, total lactic acid, total microbe, solubility, viability, and flavour and taste. The concentration of starter also had highly significant effect on total solid, protein content, total lactic acid, total microbe, solubility, viability, and flavour and taste, and had a significantly effect on total soluble solid. The interaction of the two factors had highly significant effect on total microbe and viability. The concentration of milk powder of 16% and concentration starter of 4% produced the best quality of instant juicy tuber yogurt.